Perancangan Sistem Hydrant Menurut Standart NFPA 14 Dan 20 Pada Gudang PT. Indaco Warna Dunia - Ariansyah Malik; Audito Bintang Mahesa; Aulia' Bintang Mahanani; Alung Nanda Permana; Dika Ayu Safitri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
PT. Indaco Warna Dunia, as a leading company in the color and paint industry, is committed to the safety of employees, company assets, and the surrounding environment. In the author's view, it is necessary to design a fire extinguishing system in accordance with applicable standards and regulations at points in the room that pose a fire risk in the PT. Indaco Warna Dunia’s warehouse. The data processing process follows NFPA 14 and NFPA 20 standards. This research begins by collecting data such as warehouse layout projections for PT. Indaco Warna Dunia and building conditions, as well as other necessary technical data. This research requires the determination of hydrant locations, pump room design, reservoir design, total head calculation, hydrostatic pressure, and friction loss. The result of this research is the hydrant design in the PT. Indaco Warna Dunia’s warehouse which includes 1 point, namely the hydrant box inside the warehouse containing Hose Nozzle, Fire Hose, Hydrant Valve, Hose Rack. The required pump room area is 10 m2 with a length of 4m and a width of 2.5m, the pressure on the hydrant pump is 1 bar, the friction loss that occurs is 8.475 psi/ft, then for friction loss calculations with SI units, it is 4.98 bar/minute.